Sosialisasi moderasi beragama: pemahaman islam wasathiyah di taman pendidikan al quran (tpq) nurul muttaqin desa plaosan wonosari malang - Rivana, Rezza (Maliki Interdisciplinary Journal, 2025)
This article focuses on discussing the importance of the importance of religious moderation as a solution to the creation of social conditions in a religious society through socialization carried out at TPQ Nurul Muttaqin, Hamlet, Hamlet. society through socialization held at TPQ Nurul Muttaqin, Plaosan Hamlet, Plaosan Village, Wonosari District, Malang Regency. Plaosan, Plaosan Village, Wonosari District, Malang Regency. Based on naqli and aqli arguments, this socialization explains how the urgency of applying a moderate attitude in religion.The essence of religious moderation is the concept of wasathiyyah Islam which includes five main characters: being in the middle, understanding religion deeply, being fair, and practicing moderation. The application of religious moderation can be done in two directions, namely in the internal and external aspects of Islam.